2015
DOI: 10.4049/jimmunol.1401851
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Pbx1-d Lupus Susceptibility Allele Accelerates Mesenchymal Stem Cell Differentiation and Impairs Their Immunosuppressive Function

Abstract: Pre–B cell leukemia homeobox 1 (Pbx1)-d is a dominant-negative splice isoform of the gene Pbx1 that corresponds to the NZM2410 lupus susceptibility locus Sle1a1. Pbx1 is required to maintain stem cell self-renewal, including that of mesenchymal stem cells (MSCs). MSCs have immunosuppressive functions that require stem cell maintenance. We tested the hypothesis that the expression of Pbx1-d favors MSC differentiation and impairs their immunosuppressive functions. We demonstrate that Sle1a1 MSCs express high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…B6. Sle1a1 mice express Pbx1-d in other cell types, such as mesenchymal stem cells, leading to an increased production of pro-inflammatory cytokines (21). Pbx1 also regulates the production of inflammatory cytokines in macrophages in response to apoptotic cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B6. Sle1a1 mice express Pbx1-d in other cell types, such as mesenchymal stem cells, leading to an increased production of pro-inflammatory cytokines (21). Pbx1 also regulates the production of inflammatory cytokines in macrophages in response to apoptotic cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…1B and C). Primer and Taqman probe sequences used to measure Pbx1-d message expression have been described (21). Mice from all four lines were healthy at least up to one year of age.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, expression profiles of genes related to immune function in SLE MSCs, such as IDO, IL-6, IL-7, and TGF-β, are distinct from those in normal subjects [ 17 , 37 39 ]. Correspondingly, the function of MSCs from SLE patients or lupus animal models is severely damaged and not sufficient to suppress various immune cells [ 40 , 41 ], and may thus contribute to the onset of autoimmunity.…”
Section: Impaired Immune Regulation Of Sle Mscsmentioning
confidence: 99%
“…Besides acquired immunity, the abnormality of innate immunity in SLE is also related to MSCs [ 40 ]. Macrophages from either lupus mice or SLE patients display decreased CD206 expression and inefficient phagocytic activity that could be corrected by MSCs from a healthy population in an IL-6-dependent manner [ 29 ].…”
Section: Impaired Immune Regulation Of Sle Mscsmentioning
confidence: 99%
“…Pbx1 -deficient embryonic stem cells fail to generate common lymphoid progenitors, resulting in the absence of B and NK cells, as well as an impaired T cell development (Sanyal et al, 2007). Accordingly, we have shown that mesenchymal stem cells (MSC) from mice expressing Sle1a1 show an accelerated lineage differentiation and expression of innate inflammatory genes, as well as an impaired immunoregulatory capacity (Lu et al, 2015), which corresponds to defects reported in MSCs from lupus patients as well as lupus-prone mice (Collins and Gilkeson, 2013). These complex regulatory networks regulated by reflect the ability of Pbx1 complexed with either Meis or Prep1 to recruit a wide array of Hox and non-Hox co-factors, many of which vary between cell types, and to direct either gene activation or repression (Laurent et al, 2008).…”
Section: Introductionmentioning
confidence: 99%